2013
DOI: 10.1093/carcin/bgt109
|View full text |Cite
|
Sign up to set email alerts
|

The PML isoform IV is a negative regulator of nuclear EGFR’s transcriptional activity in lung cancer

Abstract: Epidermal growth factor receptor (EGFR) is a membrane-bound receptor tyrosine kinase, which can transduce intracellular signals responsible for cell proliferation. It is frequently overexpressed and/or constitutively activated in non-small cell lung cancer and thus is considered as a major cause of this disease. Recently, EGFR has been found in the nucleus where the nuclear EGFR (nEGFR) can function as a transcription factor activating the transcription of genes such as cyclin D1 gene (CCND1), which is essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
3
10
0
Order By: Relevance
“…Notably, a specific PML isoform with a molecular mass of 95 kDa interacted with Pin1 and corresponded to the most extensively studied isoform ( Figure 7A). 19,20 Consistent with our co-IP results, PML and Pin1 were found co-localized under confocal microscopy in cultured NMCFs. Pin1 exhibited a diffuse distribution throughout the nucleus and a partial colocalization with PML (Figure 7B).…”
Section: Regulation Of Cardiac Fibrogenesis By Pml Sumoylation Througsupporting
confidence: 87%
“…Notably, a specific PML isoform with a molecular mass of 95 kDa interacted with Pin1 and corresponded to the most extensively studied isoform ( Figure 7A). 19,20 Consistent with our co-IP results, PML and Pin1 were found co-localized under confocal microscopy in cultured NMCFs. Pin1 exhibited a diffuse distribution throughout the nucleus and a partial colocalization with PML (Figure 7B).…”
Section: Regulation Of Cardiac Fibrogenesis By Pml Sumoylation Througsupporting
confidence: 87%
“…As shown in Figure 8a, Flag tagged WT and DM PML demonstrated similar protein expression levels. Consistent with previous report [36], WT PML-expressing cells depicted a significant growth inhibition compared with that of vector expressing cells, as assessed by CCK-8 assay. Intriguingly, we found that DM PML expressing cells completely lost this growth inhibition effect (Figure 8b), suggesting that association of PML with LC3 may facilitate PML-conducted growth inhibition.…”
Section: Resultssupporting
confidence: 92%
“…However, lack of nuclear transport of proteins containing NLS sequence in this cell line has already been presented [41]. Similar to our observations, EGFR containing a tripartite NLS (RRRHIVRKRTLRR) was detected in nucleus of HCC827 cells but was barely detectable in nuclear compartment of A549 cells [42,43]. These findings suggest that importins-dependent route in A549 is not efficient as compared to other cell lines.…”
Section: Resultssupporting
confidence: 90%